Culture and Urban Policies: Dynamics and Effects of Cultural Third Sector Interventions in Barcelona - Nicolás Barbieri; Xavier Fina; Joan Subirats (Métropoles)
This article addresses three interrelated questions, which we consider to be significant in current debates surrounding the future of cities. What constitutes an urban policy and what are the main variables that characterise it ? To what extent have cultural policies adopted the core features of urban policies ? And above all, what part does the third sector play in transforming the categories of social organisation that sustain urban and cultural policies ? This article argues, via a Barcelona case study, that third sector organisations play a central role in the development of cultural policies as urban policies. This is essentially because these organisations have developed their own intervention logic, which is representative of a certain type of cultural and urban intervention. From this perspective, to what extent might the proximity factor regain value as a guide to cultural and urban policies ?